Iron supplementation reduces the erosive potential of a cola drink on enamel and dentin in situ - Melissa Thiemi Kato; Marília Afonso Rabelo Buzalaf (University of São Paulo, 2012)
Iron has been suggested to reduce the erosive potential of cola drinks in vitro.OBJECTIVE: The aim of this study was to evaluate in situ the effect of ferrous sulfate supplementation on the inhibition of the erosion caused by a cola drink. MATERIAL AND METHODS: Ten adult volunteers participated in a crossover protocol conducted in two phases of 5 days, separated by a washout period of 7 days. In each phase, they wore palatal devices containing two human enamel and two human dentin blocks. The volunteers immersed the devices for 5 min in 150 mL of cola drink (Coca-ColaTM, pH 2.6), containing ferrous sulfate (10 mmol/L) or not (control), 4 times per day. The effect of ferrous sulfate on the inhibition of erosion was evaluated by profilometry (wear). Data were analyzed by paired t tests (p<0.05). RESULTS: The mean wear (±se) was significantly reduced in the presence of ferrous sulfate, both for enamel (control: 5.8±1.0 µm; ferrous sulfate: 2.8±0.6 µm) and dentin (control: 4.8±0.8 µm; ferrous sulfate: 1.7±0.7 µm). CONCLUSIONS: The supplementation of cola drinks with ferrous sulfate can be a good alternative for the reduction of their erosive potential. Additional studies should be done to test if lower ferrous sulfate concentrations can also have a protective effect as well as the combination of ferrous sulfate with other ions.